Physiological, hematological, and biochemical parameters of the Molina’s hog-nosed skunk (Conepatus chinga) - Fabiane de Holleben Camozzato Fadrique; Lorena Eduarda Feitosa Ferrarezi da Silva; Daniele Gehres; Luiz Fernando Minello; Bruna Zafalon-Silva; Belise Maria Oliveira Bezerra; Ana Raquel Mano Meinerz; Raqueli Teresinha França (Comparative Clinical Pathology, 2026)
Abstract Species-specific physiological and clinicopathological information remains limited for many small Neotropical carnivores, including Conepatus chinga. This study aimed to provide preliminary descriptive observations of physiological measurements obtained under isoflurane anesthesia and hematological and biochemical results from rescued free-ranging Conepatus chinga individuals considered clinically healthy at the time of sampling. Seven individuals from an opportunistic convenience sample were evaluated as part of routine clinical and pre-release assessment at the Wildlife Rehabilitation Center of the Federal University of Pelotas. Heart rate, respiratory rate, and rectal temperature were measured under isoflurane anesthesia. Blood samples were collected from the ventral coccygeal vein in pups and from the left or right jugular vein in juvenile and adult individuals for complete blood counts and biochemical analyses. Individual values, arithmetic mean ± sample standard deviation, and median with first and third quartiles were reported. Heart rate ranged from 152 to 240 bpm, with a median of 210 bpm; respiratory rate ranged from 15 to 28 mpm, with a median of 24 mpm; and rectal temperature ranged from 34.9 to 37.5 °C, with a median of 36.3 °C. Packed cell volume ranged from 19.4 to 42.3%, with a median of 29.6%, and total leukocyte counts ranged from 4800 to 14,000/µL, with a median of 7800/µL. Albumin, creatinine, and urea concentrations ranged from 2.44 to 3.70 g/dL, 0.20 to 0.83 mg/dL, and 6.31 to 101.60 mg/dL, with medians of 3.21 g/dL, 0.30 mg/dL, and 79.0 mg/dL, respectively. The findings constitute preliminary descriptive observations obtained under the clinical, anesthetic, and analytical conditions of this study. They should not be interpreted as reference intervals, clinically actionable baseline values or diagnostic thresholds for C. chinga, but may assist in the design of future studies involving larger and more representative samples.